The Impact of Change in Fashion and Fabrics Coursework Requirements at Ordinary Level: A Case Study of Lower Gweru Schools in Zimbabwe - Betty Shoko; Nyembezi P. Dapira; Siphetheni Mpala (National University of Science and Technology (NUST)., 2023)
The study investigated the impact of change in Fashion and Fabrics coursework requirements from two garments to one at Ordinary Level. The study was done in 2011. A case study of four schools in the Lower Gweru cluster in the Midlands province in Zimbabwe was used to ascertain how the change has affected time usage, content coverage and skills exhibited by pupils. The one garment policy was introduced to reduce material costs paid by parents and to lessen the work on pupils. However the benefits of the policy have not translated and to a rise in the number of students registered for the subject. The descriptive survey design was used to collect data from eight teachers, four school heads and four classes of pupils. Data was collected using questionnaires, interviews and focus group discussions. The results indicated that the one garment policy has brought with it benefits such as reduced costs, ample time to finish the coursework garment and time to concentrate on other components of the syllabus. The misconception noted on the requirements of the policy was that pupils were not being exposed to adequate practical work. It is recommended that teachers should increase the number and types of garments made by pupils from Form one to Form four. Parents should also provide practical requirements on time so that pupils and teachers alike may enjoy the benefits of the one garment policy. Key words: coursework, materials, Fashion and Fabrics, practical skills.